Adsorption of U(VI) from Aqueous Solution onto Hydrotalcite-Like Compounds - Nguyen Van Suc (E-Journal of Chemistry)
Uranium adsorption by the synthesized compound of magnesium aluminum hydroxide hydrate – layered double hydrotalcite (STH)-like compounds was studied. The calcinated STH was proven to be a highly effective in U(VI) adsorption in pH range from 6.5 to 7. The time dependent experimental data were found to be fit to the pseudo-second-oder model. The equilibrium data have been modeled using Langmuir and Freundlich isotherms. The results showed that both model provide the best correlation with equilibrium data. The highest adsorption capacity, approximated 62.5 mg/g, was observed in the calcinated STH at 500 °C. The positive value of enthalpy change indicated that adsorption reaction of U(VI) on STH was endothermic process. The regeneration experiments of STH using 0.1M Na2CO3 solution was successfully demonstrated multiple times without any significant effect on the initial adsorption capacity.